Performan Ayam Broiler yang Diberi Ransum yang Mengandung Bungkil Kelapa yang Difermentasi Ragi Tape Sebagai Pengganti Sebagian Ransum Komersial - Budiansyah, Agus (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
The objective of the research was to study effect of using fermented copra meal with ragi tape in ration  to  replace  of  commercial  feed  diets  on  broiler  performance. One  hundreds  of  broiler  Lohman strain aged a week were randomly assigned to five dietary treatments. The treatments were consisted of two levels of copra meal without fermentation (BKTF) and two levels of copra meal with fermentation of ragi  tape  (BKFRT)  to  replace of part of  commercial  feed diets  (RK) and one  of dietary  treatment was without copra meal as a control. They were R0 = 100 percent of commercial feed diets as a control (RK); R1 = 10 percent of BKTF + 90 percent of RK; R2 = 20 percent of BKTF + 80 percent of RK; R3 = 10 percent of BKFRT + 90 percent of RK; dan R4 = 20 percent of BKFRT + 80 percent of RK.  The chicks were  fed  for  four weeks. At  the  end  of  experiment,  two  broilers  from  each units were  slaughtered  to measure  carcass  weight.  Data  from  completely  randomized  design  were  subjected  to  ANOVA  and different  among  treatments were  further  analyzed using Tukey  test. Parameters  of  the  research were feed consumption, average body weight gain, feed conversion, final body weight and carcass weight. The result of  the experiment  showed that using of copra meal with or without  fermentation used ragi tape  in broiler diets to replace commercial  feed diets were no significant effect on feed consumption, average body  weight  gain,  final  body  weight  and  carcass  weight,  but  they  had  signifacant  effect  on  feed conversion. Using of copra meal in broiler diets with or without fermentation of ragi tape (BKFRT and BKTF) at level of 20 percent were increase feed conversion. The result concluded that using copra meal in  broiler  diets with  or without  fermentation  of  ragi  tape  could  application  at  level  of  10  percent  to replace  commercial  feed  diets,  and  fermentation  of  copra  meal  used  of  ragi  tape  had  no  significant improvement on broiler performance.